An Analytical Study of Chest Girth, Vital Capacity and Respiratory Rate of Inter Collegiate Players of Selected Ball Games (Global Journal of Medical Research, 2017)
system. They supply the muscles with the necessary fuels and oxygen, and carry away waste products such as carbon-die-oxide (co2) and lactic acid. Consequently, the cardio-respiratory system in the athlete needs to be developed to match the muscles which it supplies and cleanses. It is believed that bigger the lungs and heart size greater will be the cardio-respiratory efficiency. Hence the Research Scholar undertook the present study to determine the relationship among the selected variables as well to find out the difference among the Football, Volleyball and Handball.
Keywords: chest girth; vital capacity; respiratory rate; physical education